Stelis anagraciae (Orchidaceae), a new pleurothallid species from Guatemala - Archila Morales, Fredy L.; Szlachetko, Dariusz L. (Biodiversity: Research and Conservation, 2013)
A new species of the orchid genus Stelis Sw. - S. anagraciae Archila & Szlach. - from Guatemala is described and illustrated.